2015
DOI: 10.1007/s00406-015-0666-1
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for alterations of cortical folding in anorexia nervosa

Abstract: Anorexia nervosa (AN) is highly heritable, and the perspective on the etiology of AN has changed from a behavioral to a neurobiological and neurodevelopmental view. However, cortical folding as an important marker for deviations in brain development has yet rarely been explored in AN. Hence, in order to determine potential cortical folding alterations, we investigated fine-grained cortical folding in a cohort of 26 patients with AN, of whom 6 patients were recovered regarding their weight at the time point of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 73 publications
0
9
1
Order By: Relevance
“…Nevertheless, the studies are not directly comparable, as lGI instead of AMC was applied. In contrast to our investigation, Schultz et al () and Bernardoni et al () found increased cortical folding in terms of AMC. However, it must be taken into account that Schultz et al () examined a mixed‐sex sample containing participants with acute AN and REC patients.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, the studies are not directly comparable, as lGI instead of AMC was applied. In contrast to our investigation, Schultz et al () and Bernardoni et al () found increased cortical folding in terms of AMC. However, it must be taken into account that Schultz et al () examined a mixed‐sex sample containing participants with acute AN and REC patients.…”
Section: Discussioncontrasting
confidence: 99%
“…Unlike our study, all previous studies (Bernardoni et al, ; Favaro et al, ; Miles et al, ; Schultz et al, ), used FreeSurfer instead of CAT12. In addition, no research group has yet chosen both a vertex‐ and ROI‐based approach.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…Alternatively, one can calculate local gyrification index (LGI), which provides information about the amount of cortex that is buried inside the sulci (Schaer et al, ). Both approaches have been previously used to examine cortical folding in acute AN, with two studies reporting significantly increased cortical curvature in AN (Bernardoni et al, ; Schultz et al, ) and another two reporting large‐scale reduction in local gyrification (Bernardoni et al, ; Favaro, Tenconi, Degortes, Manara, & Santonastaso, ). Taken together, these seemingly contradictory findings suggests increased sharpness of sulci and gyri in acute AN resulting in reduced cortical area inside the sulci.…”
Section: Introductionmentioning
confidence: 99%
“…Other surface-based methods, such as the local gyrification index and cortical folding, have been employed to describe brain cortical changes in patients with AN [10][11][12]. Both measures displayed significant alterations in acute patients, but the interpretation of these findings is not clear, since gyrification tends to develop early in childhood and its alteration is usually attributed to prenatal or very early insults [13].…”
Section: Introductionmentioning
confidence: 99%